THE IMPORTANCE OF INNOVATIVE BUSINESS IDEAS IN THE HEALTH CARE SYSTEM - Mirzaliyeva Lazzatkhan Madaminovna (Bright Mind Publishing, 2025)
This article comprehensively analyzes the importance of innovative business ideas in the healthcare system. Innovative ideas play an important role not only in improving the quality of medical services, but also in providing fast, convenient and effective assistance to the population. Today, telemedicine, mobile applications, diagnostic systems developed based on artificial intelligence, and startups based on biotechnology are considered the most promising areas of medicine. This study examined the impact, economic efficiency and social benefits of modern innovative projects on the healthcare sector. Reforms in the healthcare system of Uzbekistan, international experiences and future development prospects were also analyzed.
Keywords: Healthcare, innovation, business idea, medical service, telemedicine, mobile application, artificial intelligence, biotechnology, startup, healthcare management, efficiency, economic development, health monitoring, innovative technology.